ATP-binding cassette transporters as pitfalls in selection of transgenic cells - Theile, Dirk; Staffen, Bianca; Weiß, Johanna (Analytical biochemistry, 2010)
Puromycin, hygromycin, and geneticin (G418) are antibiotics frequently used to select genetically engineered eukaryotic cells after transfection or transduction. Because intrinsic or acquired high expression of ATP-binding cassette (ABC) transporters, such as P-glycoprotein (Pgp/ABCB1) and multidrug resistance-associated proteins (MRP/ABCC1), can hamper efficient selection, it is important to know whether these antibiotics are substrates and/or inducers of efflux transporters. Therefore, we investigated the influence of these antibiotics on drug transporter expression by quantitative real-time polymerase chain reaction in the induction model cell line LS180. Moreover, we assessed whether ABC transporters influence the growth inhibitory effects of these antibiotics by proliferation assays using Madin-Darby canine kidney II (MDCKII) cells overexpressing the particular transporter. The results obtained indicate that puromycin and G418 are substrates of several ABC transporters, mainly Pgp/ABCB1. In contrast, hygromycin seems to be no good substrate for any of the ABC transporters investigated. Puromycin induced ABCC1/MRP1, whereas G418 suppressed ABCB1/Pgp, at the messenger RNA (mRNA) level. In contrast, hygromycin had no effect on ABC transporter mRNA expressions. In conclusion, this study emphasizes the significance of ABC transporters for the efficacy of selection processes. Consciousness of the results is supposed to guide the molecular biologist to the right choice of adequate experimental conditions for successful selection of genetically engineered eukaryotic cells.